Artificial immunization of rabbits against Hyalomma dromedarii Effect on developmental stages of tick - KUMAR, RAJENDER; KUMAR, RAJINDER (The Indian Journal of Animal Sciences, 2013)
The feeding and moulting performances of Hyalomma dromedarii larval and nymphal stages were adversely affected when fed on the rabbits immunized with the partly fed female adult tick derived midgut concealed antigens (supernate and pellet fractions). The engorgement and moult periods of these developmental stages were significantly prolonged. Immunized animals permitted significantly reduced number of larvae and nymphs to feed upon them. Engorged weight was significantly decreased in both developmental stages (larvae and nymphe) on repletion. Animals, inoculated with both the fractions emulsified with Freund’s cbmplete adjuvant (FCA) and without FCA rejected 11-38 and 10-39% of larval and nymphal ticks respectively.